The flow over delta wings at low speeds with leading edge separation - Marsden, D. J.; Simpson, R. W.; Rainbird, W. J. (College of Aeronautics, 1958)
A low speed investigation of the flow over a 40 degree apex angle delta wing with sharp leading edges had been made in order to ascertain details of the flow in the viscous region near the leading edge of the suction surface of the wing. A physical picture of the flow was obtained from the surface flow and a smoke technique of flow visualization, combined with detailed measurements of total head, dynamic pressure, flow directions and vortex core positions in the flow above the wing.